ENVIRONMENTAL EDUCATION FROM THE PERSPECTIVE IN TEACHING GEOGRAPHY - Nascimento dos Santos, Alexandre; Bandeira de Moura, Deyvison (Revista Gênero e Interdisciplinaridade, 2025)
Environmental education is essential in the geography curriculum, promoting conscious and critical citizenship in relation to environmental challenges. This study highlights the relevance of field study methodologies, thematic maps, case studies and the use of technologies, such as Geographic Information Systems (GIS), which facilitate the practical understanding of the interactions between society and the environment. The National Common Curricular Base (BNCC) emphasizes the importance of forming environmentally responsible citizens, but the implementation of these principles depends on investments in infrastructure, teaching resources and ongoing teacher training. Activities developed in geography teaching, such as analysis of deforestation and pollution, increase ecological awareness and encourage sustainable attitudes. Therefore, integrating environmental education into geography contributes to a more balanced society committed to the preservation of natural resources.